Nations-in-renewal and the political production of ethnicity: with references to Malaysia - Ooi , Kee Beng (Universiti Kebangsaan Malaysia, 2002)
This paper argues that ethnicity results from prolonged political cohesive success. All ethnicities can point to a past whether mythological or historical or probably both, when they were politically and culturally influential. They may think of it as a period of unity, but most importantly, it was in fact their discursive genesis. Seen in its contemporary context, nation-building is thus a process within which an ethnic identity reform, if not a new ethnicity, takes place. Primordiality is not a tenable notion. Together with bodily features and discursive habits, landscapes provide a base for group identification. New monuments function therefore as new landscapes inhabited by an emerging ethnicity. Malaysia serves here as the main empirical reference